2008
DOI: 10.1037/0090-5550.53.1.63
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a substance use disorder screening instrument for use in vocational rehabilitation settings.

Abstract: The study objectives were to develop and validate a substance use disorder screening instrument for vocational rehabilitation customers. Beginning with the Substance Abuse Subtle Screening Inventory-3 (SASSI-3), the authors developed items pertaining to prescription medication misuse and modified other items. Research Method/Design: Data were collected for the cross-sectional cohort study through interviews with a random subsample reinterviewed 14 days later. Complete data sets were collected from 948 customer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…The Substance Abuse in Vocational Rehabilitation-Screener (SAVR-S; Heinemann, Lazowski, Moore, Miller, & MacAweeney, 2008) was developed to measure drug and alcohol misuse in disability samples. It is based on the Substance Abuse Subtle Screening Inventory-3 (Lazowski, Miller, Boye, & Miller, 1998) which includes items that assess a defensive response style.…”
Section: Methodsmentioning
confidence: 99%
“…The Substance Abuse in Vocational Rehabilitation-Screener (SAVR-S; Heinemann, Lazowski, Moore, Miller, & MacAweeney, 2008) was developed to measure drug and alcohol misuse in disability samples. It is based on the Substance Abuse Subtle Screening Inventory-3 (Lazowski, Miller, Boye, & Miller, 1998) which includes items that assess a defensive response style.…”
Section: Methodsmentioning
confidence: 99%
“…Reports were generated using the proprietary algorithms and results ("low", "medium", or "high" probability of having a substance use disorder) were generated. The SAVR-S has a robust sensitivity and specificity for SUD among VR applicants [38].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study of 1,000 VR applicants in the mid-west found that 22% met the Diagnostic and Statistical Manual for Mental Disorders (DSM-IV-TR) criteria for SUD [38]. These rates alone provide a valid concern for VR pro-fessionals to be aware of the volume of consumers who have either a diagnosed or undiagnosed SUD.…”
Section: Predictors Of Employment Suggest Predictors Of Unemploymentmentioning
confidence: 99%
“…This segregated approach may be due to the lack of training that rehabilitation counselors and researchers receive in substance abuse issues and/or vocational rehabilitation policies that may not be inclusive of serving consumers with substance use disorders. Although some rehabilitation researchers have recently focused on substance abuse issues, such research tends to be in the areas of identification of substance use disorders in individuals receiving rehabilitation services (Heinemann, Lazowski, Moore, Miller, & McAweeney, 2008; and accessibility concerns related to substance abuse treatment programs (West, Graham, & Cifu, 2009). Little, if any, research has focused on interventions or strategies for counseling individuals with disabilities and substance use disorders.…”
Section: A Convergence Of Research On Adaptation and Recovery The Impmentioning
confidence: 99%